Fibrin platelet rich in used for preservation of fence post extraction: Case Report - Cámara, Dora (2017)
The platelet-rich fibrin is a platelet concentrate of second generation, from which we can get a clot or a membrane with large number of growth factors, leukocytes and Cytokines, this is achieved by activating the chain through coagulation the centrifugation of autologous blood. In this Protocol not manipulated chemically blood, making it an accessible and simple technique to be used in daily clinical practice. This case describes the preservation of post extraction of the root remnant of the 1.5 piece flange. through Atraumatic extraction and the use of platelet-rich fibrin obtained Choukroun as biomaterial of regeneration Protocol. Fibrin clot was divided into two parts, a part as filler material autologous (osteoinductive, osteoconductive) and other such as autologous membrane to prevent the collapse of the alveoli. The clinical and radiographic evaluation of follow-up (1 month and 12 months), there is evidence of the regeneration of the area intervened and favorable clinical evo